#### (i) (a + b)^{2} + (a – b)^{2}

#### (ii) (a + b)^{2} – (a – b)^{2}

**Answer :**

**(i) (a + b)**^{2} + (a – b)^{2}

^{2}+ (a – b)

^{2}

It can be written as

= (a^{2} + b^{2} + 2ab) + (a^{2} +b^{2} – 2ab)

By further calculation

= a^{2} + b^{2} + 2ab + a^{2} + b^{2} – 2ab

So we get

= 2a^{2} + 2b^{2}

Taking 2 as common

= 2 (a^{2} + b^{2})

**(ii) (a + b)**^{2} – (a – b)^{2}

^{2}– (a – b)

^{2}

It can be written as

= (a^{2} + b^{2} + 2ab) – (a^{2} + b^{2} – 2ab)

By further calculation

= a^{2} + b^{2} + 2ab – a^{2} – b^{2} + 2ab

So we get

= 4ab

**More Solutions:**

- Trigonometric Ratios of Standard Angles
- Find the value of A if
- Find the value of θ (0° < θ < 90°) if:
- If A, B and C are the interior angles of a △ ABC
- The value of tan 30/cot60 is
- The value of (sin 45 + cos 45 ) is
- The value of tan² 30 – 4 sin² 45 is
- If A = 30, then the value of 2 sin A Cos A is
- The value of (sin 30 + cos 30) – (sin 60 + cos 60) is
- The value of √3 cosec 60 – sec 60 is